Processed meat consumption and associated factors in Chile: A cross-sectional study nested in the MAUCO cohort - Ruedlinger, Jenny; Cid-Ossandón, Vicente; Huidobro, Andrea; Van De Wyngard, Vanessa; Vargas, Claudio; Ferreccio, Catterina (Frontiers in Public Health, 2022)
Processed meat consumption is increasing in Latin America. While in developed countries processed meat consumption has been associated with cardiovascular diseases and cancer, our region lacks data associated to its consumption and health impact. We characterized processed meat intake and associated factors in a population-based cohort of a Chilean agricultural county, MAUCO. We analyzed baseline dietary data of 7,841 participants, 4,358 women and 3,483 men (38–77 years), who answered an adapted Mediterranean index food frequency questionnaire. Eight percent of the participants presented high processed meat consumption (≥5 times per week). We explored associations of processed meat consumption with participant characteristics using multinomial logistic regression models. Main factors associated with higher consumption were being men, younger and currently employed, and having a high intake (>4 times per week) of red meat (Odds ratio, 2.71, 95% CI 2.10–3.48), butter/cream (1.96, 1.60–2.41), whole-fat dairy products (1.32, 1.04–1.67) and a high intake (≥1 time per day) of sugary snacks/sweets (2.49, 2.04–3.03) and sugary drinks (1.97, 1.63–2.38). Processed meat consumption associated to chronic diseases, particularly cardiovascular disease (Prevalence ratio, 2.28, 95% CI 1.58–3.29). Obesity mediated this association in a proportion of 5.0%, whereas for diabetes the proportion was 13.9%. In this population, processed meat was associated with other unhealthy dietary and lifestyle factors, as well as with chronic diseases, particularly cardiovascular disease.